Welfare-environmental quality tradeoffs of promoting use of certified seed potato in tropical highlands of Africa: evidence from central highlands of Kenya. - Okello, J.J.; Zhou, Y.; Kwikiriza, N.; Ogutu, S.; Barker, I.; Schulte-Geldermann, Elmar; Ahmed, J.; Atieno, E. (2016)
This paper used the propensity score method to assess the effect of using certified seed potato (CSP) on yield, input use, and food security among smallholder farmers. It focused on potato growers in central highlands of Kenya. The study found positive effect using certified seed on both yield and food security. But at the same time users of CSP applied significantly higher amounts of pesticides. This study therefore concludes that while using CSP has positive welfare effects, it can increase the use of inputs, some of which have environmentally degrading effects. It discusses the policy implications of the findings.